Design and evaluation of a mobile user interface usability / Ahmad Khairul Azizi Ahmad ... [et al.] - Ahmad Khairul Azizi, Ahmad; Intan Nur Firdaus, Muhammad Fuad; Muhammad, Abdullah; Mohd Nasiruddin, Abdul Aziz (Universiti Teknologi MARA, Perak, 2018)
This research has intended to identify the importance of the usability factor in the creation of a mobile application. Basically, when it comes to directory information, most of the tourists use a conventional method, such as printed maps, traveling books, online or traveling websites and also travel agents. From my perspective and with support from the field research, language impediments and directory issues have been the most common problems in this research. While Smartphone’s and apps are, increasingly, being used nowadays, there are not sufficient studies addressing the usability of smartphone user interfaces or applications that are focused for tourist guides. This paper describes the design and evaluation process of the user interface of a smartphone application designed to be a guide or directory for tourists. Two successive versions of the user interfaces were tested with different groups. The results and findings from two rounds of usability tests led to recommendations regarding an inclusive design and the designing of apps that are useful for tourists and which may be a useful contribution to the broader community when designing interfaces for smartphones. Overall, the users enjoy using the new application that is more user friendly and easier to use and navigate with. The findings can be used as a reference to set certain standards in mobile application design and creation, and also to be used for academic benefits